2002
DOI: 10.1080/09674845.2002.11783656
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor blocking agents: a new therapeutic modality for inflammatory disorders

Abstract: Development of anti-tumour necrosis factor-alpha (anti-TNF alpha) treatment offers the potential to alter radically the course of inflammatory diseases such as rheumatoid arthritis and Crohn's disease using modalities directed against a specific inflammatory mediator. Controlled randomised trials in these diseases demonstrate clinical benefit associated with significant improvement in patients with severe active joint and intestinal disease, often when conventional therapies are unsuccessful. To date, anti-TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…30 Based on the pharmacological data available, huTNFR:Fc doses used in this study are well tolerated in humans. 5 …”
Section: Usage Of a Clinically Approved Anti-tnfa Drugmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Based on the pharmacological data available, huTNFR:Fc doses used in this study are well tolerated in humans. 5 …”
Section: Usage Of a Clinically Approved Anti-tnfa Drugmentioning
confidence: 99%
“…4 As a proinflammatory cytokine, tumor necrosis factor alpha (TNFa) is heavily implicated in the initiation and progression of autoimmune inflammatory disorders. 5,6 However, its role in Ad-induced toxicity has not been extensively studied. Although some studies found no elevation of TNFa following Ad injection, [7][8][9][10] other studies have found that TNFa release is in fact a consequence of higher-dose vector application in mice and nonhuman primates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with RA, AS or PsA, the introduction of anti-tumour necrosis factor (TNF)-a therapies such as etanercept, infliximab and adalimumab has had a significant impact in ameliorating the signs and symptoms of disease, improving patient function and inhibiting radiographic progression (10)(11)(12). Anti-TNF-a therapies now have well recognized safety profiles that have been demonstrated in the usual clinical trial populations for these diseases (18), but such populations under-represent patients > or =65 years of age.…”
mentioning
confidence: 99%
“…TNF is the prototypical proinflammatory cytokine (13). The overproduction of TNF has been associated with a number of autoimmune pathologies (14), and interfering with TNF production often ameliorates autoimmune manifestations (15). IL-12 production is associated with Th1 responses, and its role in host defense to intracellular pathogens has been well established (16).…”
mentioning
confidence: 99%